How to have creative ideas : 62 exercises to develop the mind - Debono, Edward (London : Vermilion, 2007)
Edward De Bono outlines 62 different games and exercises, built around random words chosen from a list, to encourage creativity and lateral thinking.
Keywords: Creative thinking